DIGITAL HEALTH MONITORING: EXAMINING THE EFFECTIVENESS OF WEARABLE DEVICES IN MANAGING HYPERTENSION. A BIBLIOMETRIC ANALYSIS - G. Samhita Priyadarsini, Shatha Taha, Dr U.G.Lashari, Dr. D. Vinay Kumar, Dr. Prasanta Kumar Parida, Dr. Muhammad Khan (South Eastern European Journal of Public Health, 2025)
Background: Digital health monitoring through wearable devices is a rapidly evolving field, offering innovative solutions for managing chronic conditions like hypertension. This study investigates the research landscape on wearable devices for hypertension management using bibliometric methods. Objective: To analyze the publication trends, geographical contributions, leading authors and institutions, key journals, and focal areas of research related to wearable devices in hypertension management from 2005 to mid-2024. Methods: A bibliometric analysis was conducted using the Web of Science Core Collection, focusing on English-language articles and reviews published between January 1, 2005, and June 30, 2024. A total of 1,024 publications were analyzed, comprising 710 research articles and 314 review articles. Results: • Publication Trends: The field has shown steady growth, peaking at 140 publications in 2023. • Geographical Contributions: o The USA emerged as the most active contributor, with 287 publications and 15,678 citations. o Significant contributions were also observed from Europe and Asia, particularly China and Japan. • Leading Authors and Institutions: o Prominent authors include Smith (Stanford University), Li Qian (Tsinghua University), and Brown Albert (Imperial College London). o Stanford University published the highest number of articles, while the University of Oxford's articles received the highest citation frequencies. • Key Journals: The leading journals publishing on this topic include the Journal of Medical Internet Research, Sensors, and JMIR mHealth and eHealth. • Key Terms: Common industry terms include ‘blood pressure monitor,’ ‘digital health,’ ‘telemedicine,’ ‘self-management,’ and ‘patient engagement.’ Conclusion: Wearable devices play a vital role in hypertension management, emphasizing the importance of continuous blood pressure monitoring and patient involvement. Telemedicine serves as a critical aid in these efforts. Future research should focus on fostering international collaborations and integrating multidisciplinary approaches to enhance the efficiency and accessibility of digital health solutions for hypertension treatment.